Isolasi dan Identifikasi Bakteri Asam Laktat dari Fermentasi Anggur Buah Pala (Myristica fragrans Houtt) Sebagai Penghasil Eksopolisakarida - Lawalata, Helen Joane; Rompas, Christny Ferdina; Kansile, Elma Fridayanti (Universitas Negeri Manado, 2020)
. Nutmeg fruit is widely used in the medicine formula and also various kinds of processed foods and beverages. Nutmeg meat can be processed into syrup, fruit juice, jam, dodol pala and wine. The fruit is believed to be one of the natural habitats of bacteria, including lactic acid bacteria (BAL). The study aims to determine the type of BALES isolated in nutmeg grapes (Myristica fragrans Houtt) which has the ability to produce exopolysaccharides. Based on the results of the study obtained 15 BAL isolates namely AP1, AP2, AP3, AP4, AP5, AP6, AP7, AP8, AP9, AP10, AP11, AP12, AP13, AP14, and AP15. The exopolysaccharides produced by the isolates are 400 mg/L, 530 mg/L, 1200 mg/L, 730 mg/L, 60 mg/L, 460 mg/L, 600 mg/L, 200 mg/L, 930 mg/L, 1130 mg/L, 200 mg/L, 130 mg/L, 1000 mg/L, 800 mg/L. The next 15 isolates are identified using the profile matching method. The results of the identification show that 15 BAL isolates were included in the genus Lactobacillus and are a species of Lactobacillus bulgaricus. Keyword : Isolation, Identification, nugmeg grapes (myristica fragrans houtt), lactic acid bacteria, exopolysaccharides